Differences in the situational evaluation of goalkeeper efficiency in handball based on gender and shooting positions - Cvenic, J.; Faj, L.; Brkic, M. (10th International scientific conference on kinesiology. Book of abstracts, 2024)
The aim of the study was to determine situational efficiency of goalkeepers through the suitable created survey according to the criterion of the difficulty of the shots from different playing positions and from different situations in the game. The sample of entities consisted of 30 goalkeepers, aged 18-45, of which 15 are male and 15 are female. The sample of variables consisted of the 7 different shots from different position and distances in handball game. The differences between male and female goalkeepers evaluating were determined using the Mann-Whitney U-test, and between different player position using Kruskal Wallis test. The results showed statistically significant differences between 9m shots and all other shots, Significant difference can be noted between 9m and all other playing positions, and also between close shots (6m, 7m, wing shot) and situational shots (fast break, breakthrough, fast trow-off). Differences in defense assessment by goalkeeper gender was in the one variable: shots from 9m line (5.4 vs. 4.2; on a scale 1-10).